Reading in the (post)digital age: Large databases and the future of literature in secondary English classrooms. (2nd July 2020) - McLean Davies, Larissa; Bode, Katherine; Martin, Susan K.; Sawyer, Wayne
ABSTRACT: While "born digital" artefacts such as video games and e-books have been part of secondary school English in Anglophone countries for over two decades, databases of mass-digitised (hence "re-mediated") literary texts are yet to have a significant presence in, or influence on, literary work in subject English. The authors contend that engagement with these digitised texts requires a postdigital "literary literacy". They explore how "distant reading" – applying digital tools to large-scale data to identify patterns beyond the scale of human perception – offers a form of postdigital literary literacy that can be enacted alongside others, including productive reading and code switching. Using the example of the To be continued… database of fiction originally published in 19th and 20th century Australian newspapers, the article argues that postdigital literary objects offer new literary knowledge and new ways of thinking about literary study and teacher expertise in English in the 21st century.